Behavioural Genetics for Education - Kovas, Y.; Malykh, S.; Gaysina, D. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Educational environments interact with children's unique genetic profiles, leading to wide individual differences in learning ability, motivation, and achievement in different academic subjects - even when children study with the same teacher, attend the same school and follow the same curriculum. This book considers how education can benefit from the recent progress in genetically informative research. The book provides new insights into the origins of individual differences in education traits such as cognitive abilities and disabilities; motivation and personality; behavioural and emotional problems; social functioning; well-being, and academic achievement. Written and edited by international interdisciplinary experts, this book will be of interest to teachers, parents, educational and developmental psychologists, policy makers and researchers in different fields working on educationally-relevant issues.